COMMUNICATIVE LANGUAGE TEACHING IN ENGLISH LANGUAGE TEACHING METHODOLOGY - Choriyev Botir; Norqobilov Quddus (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract Communicative Language Teaching (CLT) is one of the most influential approaches in modern language education. It emphasizes the ability to use language for meaningful communication rather than only memorizing grammar rules. This article discusses the main principles of CLT, its historical background, classroom procedures, advantages, and possible limitations. The paper also shows why CLT remains important in English language teaching today. The analysis is based on a review of methodological literature and on the practical needs of language learners who must develop communicative competence in real-life situations.